THE MODERATING ROLE OF INTELLECTUAL CAPITAL ON THE RELATIONSHIP BETWEEN NON PROFIT SHARING FINANCING, PROFIT SHARING FINANCING AND CREDIT RISK TO FINANCIAL PERFORMANCE OF ISLAMIC BANK - Binar Arum Nurmawati; Aulia Fuad Rahman; Zaki Zaki Baridwan (Universitas Muhammadiyah Malang, 2020)
The purpose of this study is to provide empirical evidence of the effect of non profit sharing finance, profit sharing finance and credit risk on financial performance with the integration of intellectual capital as a moderating variable. The population is all Islamic banking registered in OJK for the period 2015-2018 with a total of 192 observations. These are analyzed using hierarchical regression techniques, multiple linear regression tests and moderated regression analysis (MRA) tests, with e-views 9 software. The results show that non profit sharing financing, profit sharing financing and intellectual capital have a positive and significant effect to financial performance on Islamic banking. While credit risk has a significant negative effect to financial performance of Islamic banking. Furthermore showed that intellectual capital significantly moderates the relationship of non profit sharing finance and profit sharing finance to financial performance Islamic banks. However intellectual capital can’t be moderates the relationship of credit risk and financial performance.